Determinants of Employees' Job Satisfaction - A Study on B. Braun Medical Supplies Sdn. Bhd. - Yap, Fei Looi (2009)
This study therefore aims to identify the determinants of employees\' job satisfaction among sales and marketing employees, as well as to examine the effect of job satisfaction on organizational commitment (affective commitment, continuence commitment and normative commitment).